Square pyramids and stacked spheres.

Level pending

Let V P V_{P} be the volume of the largest square pyramid that can be inscribed in a sphere of radius R R .

Each sphere inscribed in the square pyramid above are tangent to each other and stacked vertically and is extended to an infinite number of inscribed spheres. Let V s ( n ) V_{s}(n) be the volume of the n n th stacked sphere and V T = n = 1 V s ( n ) V_{T} = \displaystyle\sum_{n = 1}^{\infty} V_{s}(n) .

If V T R 3 \dfrac{V_{T}}{R^3} = a b π c b ϕ a c b ϕ + ( c a ) a \dfrac{a^b\pi}{c^{b}\phi^{a} - c^{b}\phi + (c^{a})^{a}} , where a , b a,b and c c are coprime positive integers

and ϕ \phi is the golden ratio, find a + b + c a + b + c .


The answer is 10.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Rocco Dalto
Dec 21, 2019

Let V p = 1 3 x 2 H V_{p} = \dfrac{1}{3}x^2H and V s = 4 3 π R 3 V_{s} = \dfrac{4}{3}\pi R^{3} .

x 2 2 + H 1 2 2 H 1 R + R 2 = R 2 x 2 = 4 H 1 R 2 H 1 2 \dfrac{x^2}{2} + H_{1}^2 - 2H_{1}R + R^2 = R^2 \implies x^2 = 4H_{1}R - 2H_{1}^2 \implies

V p = 2 3 ( 4 H 1 2 R 2 H 1 3 ) d V p d H 1 = V_{p} = \dfrac{2}{3}(4H_{1}^2R - 2H_{1}^3) \implies \dfrac{dV_{p}}{dH_{1}} = 2 3 ( 4 H 1 R 3 H 1 2 ) = 0 H 1 ( 4 R 3 H 1 ) = 0 \dfrac{2}{3}(4H_{1}R - 3H_{1}^2) = 0 \implies H_{1}(4R - 3H_{1}) = 0

and x 0 H 1 = 4 3 R x = 4 3 R = H 1 x \neq 0 \implies H_{1} = \dfrac{4}{3}R \implies x = \dfrac{4}{3}R = H_{1}

The slant height s = 5 2 x = 4 3 ( 5 2 ) R s = \dfrac{\sqrt{5}}{2}x = \dfrac{4}{3}(\dfrac{\sqrt{5}}{2})R

and the area of the above triangle is A = 1 2 x 2 = 1 2 x r 1 + 1 2 ( 2 s r 1 ) = A = \dfrac{1}{2}x^2 =\dfrac{1}{2}xr_{1} + \dfrac{1}{2}(2sr_{1}) =

r 1 2 ( x + 2 s ) r 1 = x 2 x + 2 s = x 5 + 1 = \dfrac{r_{1}}{2}(x + 2s) \implies r_{1} = \dfrac{x^2}{x + 2s} = \dfrac{x}{\sqrt{5} + 1} = 4 3 ( 5 + 1 ) r 1 \dfrac{4}{3(\sqrt{5} + 1)}r_{1}

Let ϕ = 5 + 1 2 r 1 = 2 R 3 ϕ \phi = \dfrac{\sqrt{5} + 1}{2} \implies r_{1} = \dfrac{2R}{3\phi}

R = 3 ϕ 2 r 1 H 1 = 4 3 R = 4 3 ( 3 ϕ 2 ) r 1 = 2 ϕ R 1 \implies R = \dfrac{3\phi}{2}r_{1} \implies H_{1} = \dfrac{4}{3}R = \dfrac{4}{3}(\dfrac{3\phi} {2})r_{1} = 2 \phi R_{1}

and H 2 = H 1 2 r 1 = 2 ( ϕ 1 ) r 1 H 1 H 2 = ϕ ϕ 1 H 2 = ( ϕ 1 ϕ ) H 1 H_{2} = H_{1} - 2r_{1} = 2(\phi - 1)r_{1} \implies \dfrac{H_{1}}{H_{2}} = \dfrac{\phi}{\phi - 1} \implies H_{2} = (\dfrac{\phi - 1}{\phi})H_{1}

Let j = ϕ 1 ϕ < 1 j = \dfrac{\phi - 1}{\phi} < 1 , then r 1 = 2 R 3 ϕ r 2 = j r 1 r 3 = j r 2 = j 2 r 1 r_{1} = \dfrac{2R}{3\phi} \implies r_{2} = jr_{1} \implies r_{3} = jr_{2} = j^2r_{1} and in general

r 1 = 2 R 3 ϕ r_{1} = \dfrac{2R}{3\phi} and for each positive integer n 1 ( r n + 1 = j n r 1 ) n \geq 1 \:\ (r_{n + 1} = j^n r_{1})

\therefore The Total Volume V T = 4 π 3 r 1 3 + 4 π 3 r 1 3 n = 1 ( j 3 ) n = V_{T} = \dfrac{4\pi}{3}r_{1}^3 + \dfrac{4\pi}{3}r_{1}^3\displaystyle\sum_{n = 1}^{\infty} (j^3)^n =

4 π 3 r 1 3 n = 1 ( j 3 ) n 1 = \dfrac{4\pi}{3}r_{1}^3\displaystyle\sum_{n = 1}^{\infty} (j^3)^{n - 1} = 4 π 3 r 1 3 ( 1 1 j 3 ) \dfrac{4\pi}{3}r_{1}^3(\dfrac{1}{1 - j^3}) \implies

V T = 4 π 3 ( 8 R 3 27 ϕ 3 ) ( ϕ 3 ϕ 3 ( ϕ 1 ) 3 ) = V_{T} = \dfrac{4\pi}{3}(\dfrac{8R^3}{27\phi^3})(\dfrac{\phi^3}{\phi^3 - (\phi - 1)^3}) =

( 32 81 ) ( 1 3 ϕ 2 3 ϕ + 1 ) π R 3 = 2 5 π 3 5 ϕ 2 3 5 ϕ + ( 3 2 ) 2 R 3 (\dfrac{32}{81})(\dfrac{1}{3\phi^2 - 3\phi + 1})\pi R^3 = \dfrac{2^5\pi}{3^5\phi^2 - 3^5\phi + (3^{2})^2}R^3

V T R 3 = 2 5 π 3 5 ϕ 2 3 5 ϕ + ( 3 2 ) 2 \implies \dfrac{V_{T}}{R^3} = {\dfrac{2^5\pi}{3^5\phi^2 - 3^5\phi + (3^{2})^2}} = a b π c b ϕ a c b ϕ + ( c a ) a a + b + c = 10 = \dfrac{a^b\pi}{c^{b}\phi^{a} - c^{b}\phi + (c^{a})^{a}} \implies a + b + c = \boxed{10}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...